CURRENT ISSUES OF RENTING COMMERCIAL PREMISES IN MARKET TIMES (Journal of actual problems of jurisprudence, 2025)
The article deals with the current issues of commercial space rental in the market era. Currently, the author suggests measures related to the affordability of renting a space for anyone. The main objective of the research article is to address the causes and effects of the current problems and obstacles. Among the research methods in the article, we include survey and comparative legal methods. As a result of the survey conducted among government officials, businessmen, students and individuals, the author evaluates the activities of room renting and suggests ways of its effective implementation in the interest of the society.In the theoretical preparation of the article the advanced works of lawyers in the world arena on the topic of leasing commercial premises and the main works of domestic criminologists, statistical analysis and conclusions were used.Result of the article: increase in gross domestic product as the main way to reduce inflation and price increases in the rental of commercial premises; state subsidies to organisations engaged in non-residential and residential construction, as well as in the production of construction materials; work to increase the willingness of sellers and buyers to sell domestic products; increase competition (especially from the state) to positively affect the quality and price of construction works (services); Attracting foreign construction companies, they have to::in order to increase the market competitiveness of domestic companies and the requirement to create favourable conditions for working youth and support socially vulnerable segments of the population; to create special economic zones and provide for tax, customs duties and other mandatory payments to the budget for companies operating there; to increase the legal culture of the population in matters of housing purchase and sale transactions; Transfer of the queue in akimats to a family bank system consisting of persons in need of housing.Keywords: market century, commercial space, leasing, buying and selling, investment, gross domestic product, household goods, construction companies.